Attempt at taxonomical characterization of some Rhizobial species by intact cell MALDI mass spectrometry - Prabhu, R. R.; Kulkarni, Mahesh J.; Parasharami, V. A.; Santhakumari, B.; Paranjape, S. (World Journal of Microbiology & Biotechnology, 2007)
In the present study an attempt was made to exploit the benefit of intact cell MALDI mass spectrometry (ICM-MS) in bringing out similarities and differences among some Rhizobium species and a species of Agrobacterium based on specific mass:charge (m/z) values. Rhizobium species isolated from the root nodules of selected leguminous plants were analysed by ICM-MS. The spectra were acquired in the range of 500-10,000 Da yielding several peaks specific to each species. The peaks obtained corresponded to the respective bacterial cell surface molecules which were desorbed during matrix-assisted laser desorption ionization. The number of peaks were more in the range of 500-1200 Da. Dice similarity coefficient analysis of m/z values indicated that Rhizobium species isolated from Trigonella foenum-graecum and Pisum arvense showed more similarity than any other species. Agrobacterium species did show a few common m/z values in comparison with other Rhizobium species. This clearly shows that Agrobacterium is closely related to Rhizobium. Eventually, ICM-MS technique offers clear, distinct, and consistent results for replicates, in less than an hour's time, therefore this technique has high potential in molecular taxonomy.
Keywords: ICM-MS; legume; molecular taxonomy; Rhizobium; symbiotic